Why Are Federal Judges So Acquittal Prone? - Andrew D. Leipold (Washington University Law Quarterly, 2005)
Federal criminal defendants almost always prefer a jury trial to a bench trial, but it is unclear why. Statistically, federal judges are significantly more likely to acquit than a jury is—over a recent 14 year period, for example, the jury trial conviction rate was 84%, while the bench conviction rate was a mere 55%. Moreover, while the conviction rate for juries has remained nearly constant for many years, the judicial rate has fallen steadily since the late 1980s. This Article presents the first systematic attempt to explain this “conviction gap.” Using original compilations of government records on over 75,000 federal criminal trials, this Article explores a variety of possible stories that would explain why judges and juries behave so differently. It concludes that some, but not all, of the gap can be explained by identifiable features of those cases that defendants direct toward judges rather than juries. It also concludes, however, that the recent changes in judicial behavior cannot be fully explained on these grounds; instead, the Article hypothesizes that the federal sentencing scheme, which changed dramatically during the 80s and 90s, may well have affected the way judges evaluate the government's case in bench trials. The latter conclusions may have significant implications for the changes in federal sentencing that are likely to occur over the next several years.
Keywords: Judicial statistics; Federal judges; Acquittals; Sentencing guidelines (Criminal procedure); Judicial discretion; Judicial process; United States